2019
DOI: 10.1186/s13019-019-0839-5
|View full text |Cite
|
Sign up to set email alerts
|

Serological cytokine profiles of cardiac rejection and lung infection after heart transplantation in rats

Abstract: BackgroundAllograft rejection and infection are the major sources of morbidity and mortality after heart transplant. Early differential diagnosis is clinically crucial but difficult. The aim of the study was to examine serum cytokine profiles associated with each entity and whether such profiles could help to differentiate between them.MethodsHeart allografts from Wistar rats were transplanted to Lewis rats as described by Yokoyama. Cardiac rejection and pulmonary bacterial infection were induced by Cyclospori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The G‐CSF is associated with decreased incidence of acute rejection 31 . Interestingly, IFN‐a2, IL‐2, IL‐7, and IL‐9 have been associated to cardiovascular adverse effects and allograft rejection 32–35 . Following the ISHLT classification, 1R and 2R had elevated levels of cytokines, with a similar number of significant cytokines detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The G‐CSF is associated with decreased incidence of acute rejection 31 . Interestingly, IFN‐a2, IL‐2, IL‐7, and IL‐9 have been associated to cardiovascular adverse effects and allograft rejection 32–35 . Following the ISHLT classification, 1R and 2R had elevated levels of cytokines, with a similar number of significant cytokines detected.…”
Section: Discussionmentioning
confidence: 99%
“…31 Interestingly, IFN-a2, IL-2, IL-7, and IL-9 have been associated to cardiovascular adverse effects and allograft rejection. [32][33][34][35] Following the ISHLT classification, 1R and 2R had elevated levels of cytokines, with a similar number of significant cytokines detected. BNP analysis revealed significantly elevated BNP levels related to UC2.…”
Section: Cytokine and Bnp Levels In The Context Of The Unsupervised M...mentioning
confidence: 94%
“…However, one of the major challenges of modern transplantology still seems to be finding non-invasive, prognostic and predictive biomarkers for recipients selection, monitoring of allograft function, and diagnosis of rejection (Naesens and Anglicheau 2018 ). Several studies have associated increased cytokine production with higher risk of early and late graft rejection and suggested that these proteins may serve as markers for kidney, liver, lung, heart and HSC transplantation (Chen et al 2019 ; Friedman et al 2012 ; Hallsten and Vigneswaran 2019 ; Kawakita and Everly 2016 ; Roedder et al 2011 ; Visentainer et al 2003 ). It is well documented that cytokines modulate the T helper (Th)1 and Th2 balance.…”
Section: Introductionmentioning
confidence: 99%